On the accuracy of H I observations in molecular clouds: more cold H I than thought? - Seifried, Daniel; Beuther, Henrik; Walch, Stefanie; Syed, Jonas; Soler, Juan D.; Girichidis, Philipp; Wünsch, Richard (Monthly notices of the Royal Astronomical Society, 2022)
We present a study of the cold atomic hydrogen (H i) content of molecular clouds simulated within the SILCC-Zoom project for solar neighbourhood conditions. We produce synthetic observations of H i at 21 cm, including H i self-absorption (HISA) and observational effects. We find that H i column densities, $N_{\rm H\, \small {\rm I}}$, of ≳1022 cm−2 are frequently reached in molecular clouds with H i temperatures as low as ∼10 K. Hence, HISA observations assuming a fixed H i temperature tend to underestimate the amount of cold H i in molecular clouds by a factor of 3-10 and produce an artificial upper limit of $N_{\rm H\, \small {\rm I}}$ around 1021 cm−2. We thus argue that the cold H i mass in molecular clouds could be a factor of a few higher than previously estimated. Also, $N_{\rm H\, \small {\rm I}}$ PDFs obtained from HISA observations might be subject to observational biases and should be considered with caution. The underestimation of cold H i in HISA observations is due to both the large H i temperature variations and the effect of noise in regions of high optical depth. We find optical depths of cold H i around 1-10, making optical depth corrections essential. We show that the high H i column densities (≳1022 cm−2) can in parts be attributed to the occurrence of up to 10 individual H i-H2 transitions along the line of sight. This is also reflected in the spectra, necessitating Gaussian decomposition algorithms for their in-depth analysis. However, also for a single H i-H2 transition, $N_{\rm H\, \small {\rm I}}$ frequently exceeds 1021 cm−2, challenging one-dimensional, semi-analytical models. This is due to non-equilibrium chemistry effects and the fact that H i-H2 transition regions usually do not possess a one-dimensional geometry. Finally, we show that the H i gas is moderately supersonic with Mach numbers of a few. The corresponding non-thermal velocity dispersion can be determined via HISA observations within a factor of ∼2.